HIV/AIDS, KESEHATAN REPRODUKSI DAN ABORSI DALAM PERSPEKTIF HUKUM KESEHATAN MASYARAKAT - Gunawan Widjaja; Andina Rahmayani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Health is an element of well-being. Public health plays an important role in the formation of human resources, increasing the nation's resilience and competitiveness, as well as national development. In Indonesia, HIV infection is one of the main health problems and one of the infectious diseases that can affect maternal and child mortality. Everyone has the right to have a healthy life so that they can live productively both socially and economically, one of which is reproductive health. In principle, the state prohibits abortion, but on indications of a medical emergency and worsening mental condition due to pregnancy, cases of rape are exceptions to the provisions. The increase in cases of HIV and AIDS in the community is a potential threat to public health that can have a broad and negative impact on the resilience of the nation. In addition, the act of abortion also raises pros and cons because reproductive health is one of the scopes of public health. The purpose of making the theme of this paper is to find out the perspective of public health law on HIV and AIDS, reproductive health, and abortion. The results of this paper are the need for information disclosure, strengthening socialization, awareness and supervision of related parties in HIV and AIDS prevention, reproductive health management, and supervision of abortion.